2016
DOI: 10.7554/elife.18782
|View full text |Cite
|
Sign up to set email alerts
|

Clec11a/osteolectin is an osteogenic growth factor that promotes the maintenance of the adult skeleton

Abstract: Bone marrow stromal cells maintain the adult skeleton by forming osteoblasts throughout life that regenerate bone and repair fractures. We discovered that subsets of these stromal cells, osteoblasts, osteocytes, and hypertrophic chondrocytes secrete a C-type lectin domain protein, Clec11a, which promotes osteogenesis. Clec11a-deficient mice appeared developmentally normal and had normal hematopoiesis but reduced limb and vertebral bone. Clec11a-deficient mice exhibited accelerated bone loss during aging, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
130
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(147 citation statements)
references
References 78 publications
11
130
2
Order By: Relevance
“…Prior studies had observed Clec11a expression in bone marrow but inferred based on colony-forming assays in culture that it was a hematopoietic growth factor (Hiraoka et al, 1997;Hiraoka et al, 2001). We made germline knockout mice and found it is not required for normal hematopoiesis but that it is required for the maintenance of the adult skeleton (Yue et al, 2016). The mutant mice formed their skeleton normally during development and were otherwise grossly normal as adults but exhibited reduced adult osteogenesis and accelerated bone loss during aging (Yue et al, 2016).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Prior studies had observed Clec11a expression in bone marrow but inferred based on colony-forming assays in culture that it was a hematopoietic growth factor (Hiraoka et al, 1997;Hiraoka et al, 2001). We made germline knockout mice and found it is not required for normal hematopoiesis but that it is required for the maintenance of the adult skeleton (Yue et al, 2016). The mutant mice formed their skeleton normally during development and were otherwise grossly normal as adults but exhibited reduced adult osteogenesis and accelerated bone loss during aging (Yue et al, 2016).…”
Section: Introductionmentioning
confidence: 89%
“…To identify new growth factors that regulate hematopoiesis or osteogenesis, we performed RNA-Seq analysis on LepR + cells and looked for transcripts predicted to encode secreted proteins with sizes and structures similar to growth factors and whose function had not been studied in vivo. We discovered that Clec11a, a secreted glycoprotein of the C-type lectin domain superfamily (Bannwarth et al, 1999;Bannwarth et al, 1998), was preferentially expressed by LepR + cells (Yue et al, 2016). Prior studies had observed Clec11a expression in bone marrow but inferred based on colony-forming assays in culture that it was a hematopoietic growth factor (Hiraoka et al, 1997;Hiraoka et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 [ 35 S]UTP-labeled riboprobes used in this study were as follows: Col2a1, 34 Pthr1, 35 Col10a1, and MMP13. 37 Mineral apposition rate was measured as previously described.…”
Section: Rna In Situ Hybridization and Calcein Double Labelingmentioning
confidence: 99%
“…Examples of c-type lectins include thrombomodulin, which regulates platelet-dependent coagulation, and selectins, which control the movement of white blood cells during inflammation (Cummings et al, 2009). Now, in eLife, Rui Yue, Bo Shen and Sean Morrison at the University of Texas Southwestern Medical Center report that Clec11a, a type of c-lectin that is expressed at high levels by cells in bone marrow, stimulates bone regeneration (Yue et al, 2016). …”
mentioning
confidence: 99%